Peningkatan Keterampilan Ibu-Ibu dalam Menjahit Masker Kain sebagai Upaya Mengurangi Resiko Penularan Covid-19 - Rafael Ziku; Novita Masi Dari Tani; Liesiana Kurniawati (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
Corona Virus Disease 2019 or popularly known as COVID-19 is a contagious disease that can be deadly. Labuan Bajo, the capital of West Manggarai Regency, is a super premium tourist destination. The spread of COVID-19 has resulted in a decrease in tourist visits to Labuan Bajo. The decline in tourist visits has an impact on decreasing the income of tourism businesses in Labuan Bajo. The use of masks is one step to reduce the risk of being infected with COVID-19. Homemade cloth masks can be an alternative in anticipating the scarcity of masks amid the high public demand for masks in the atmosphere of the COVID-19 pandemic. For this reason, this activity aims to improve the skills to sew cloth masks as an effort to reduce the risk of COVID-19 transmission and provide knowledge about washing techniques for masks that have been used so that they can be used again. Partners of this community service activity are the women of Wae Kelambu Village, Labuan Bajo, West Manggarai Regency. The stages of implementing community service activities include the preparation stage, the training stage and the socialization stage. Activities are carried out while maintaining distance between people involved in this activity. The result of this community service activity is that the activity partners are able to produce ready-to-use cloth masks and gain additional knowledge about how to wash cloth masks properly.